Studying of agro-ecological properties of the some soil Northern Prikaspian - M. J. Puchkov; V. M. Strukov; E. B. Hlebtsova (Юг России: экология, развитие, 2015)
The results of the study of agro-ecological particularities of topsoil fit little for wood territory east stream-hill of the plain.